Energy-optimal overtaking manoeuvres of Formula-E cars - Liu, Xuze; Fotouhi, Abbas; Auger, Daniel J. (Taylor and Francis, 2022)
Overtaking in motorsport races is a crucial action in order to gain a higher position during a race. In Formula-E, it not only requires precisely performed overtaking manoeuvres but also requires appropriate energy management which is also a crucial element in race strategy due to the limited total amount of energy on board. This study proposes the use of optimal control techniques for feasibility and energy management analysis for such a complex problem. The analysis involves two cars on a track and the goal is to find the optimal overtaking strategy under various scenarios. The results demonstrate that overtaking can be infeasible despite that there is a potential speed advantage over the target car. An overtaking manoeuvre can be executed efficiently by using higher propulsion power. When an overtaking is feasible, the energy-optimal overtaking position varies according to different initial conditions.
Keywords: Energy management; Formula E; overtaking manoeuvres; optimal control